Influence of standard heart failure therapy on readmission rate: opportunities and limitations in modern clinical practice - S. R. Gilyarevsky (Российский кардиологический журнал)
This review considers the clinical and epidemiological significance of hospitalizations for decompensated heart failure, as well as using it as an indicator of therapy effectiveness. The data on the frequency of using medications that reduce the hospitalization risk in randomized clinical trials and in real practice are presented. The reasons for inadequate prescription of drugs for the treatment of heart failure with reduced ejection fraction and their use in insufficient doses, which include therapeutic inertness and physiological limitations, as well as the need to introduce drugs with alternative mechanisms of action into clinical practice, are iscussed.